Evaluasi Sistem Informasi Manajemen Rumah Sakit Dengan Metode Technology Acceptance Model (TAM) di Rumah Sakit X - Dony Setiawan Hendyca Putra; Rizka Kurniawati (Politeknik Negeri Jember, 2019)
Hospital has implemented hospital information management system (HIMS) since 2016. one of the factors that currently plays an important role in the successful application and use of information technology is the user factor. The level of readiness of users to receive information technology has a major influence in determining the success and failure of the application of the technology. The purpose of this research is to evaluate user perception of SIMRS based on dimension Technology Acceptance Model (perceived ease of use, perceived usefulness, attitude toward using, behavioral intention, actual usage). The method of this research is quantitative descriptive research. The object of this research is SIMRS user in all unit of hospital and research subjects are all SIMRS users. The results showed that the percentage of group calculation from PEOU 0.602 dimension (60.2%), PU 0.595 (59.5%) and ATU 0.594 (59.4%) were moderate category, dimensions of BI 0.777 (77.7%) and AU 0.694 (69.4%) are in good category. It states that the user perception of SIMRS has been running well and needs to be maintained, but there are still some shortcomings that need to socialize the officers who are less supportive of the SIMRS that is the need for motivation and assistance to users who have difficulty. Because remembering one of the benefits of SIMRS the SIM will accelerate and improve the accuracy of the transaction because everything is recorded and communicated between various units.